ショウワキチ ニ オケル ヤサイ サイバイ - 松田, 達郎; マツダ, タツロウ; MATSUDA, Tatsuro (国立極地研究所, 1968)
P(論文) The experimental cultivation of vegetables was carried out at Syowa Station by the wintering party of the 7th Japanese Antarctic Research Expedition. Vegetables were cultivated in the room, using an artificial light and chemical fertilizer, with artificial soil or with sand taken from the vicinity of Syowa Station. Radish was the main species of cultivated vegetables and the cultivation was continued throughout the wintering season. The fresh vegetables gave variety to daily meals, but a more important fact was that the wintering party members very much enjoyed growing plants in such a barren environment. departmental bulletin paper